Development of Flipped Classroom Based Guided Inquiry Learning System with Digital Literacy Using Discord Application on Thermochemistry - Ezra Delfianza; Mawardi Mawardi; Okta Suryani (Jurnal Penelitian Pendidikan IPA, 2023)
The era of the industrial revolution 4.0, teachers will deal with children who are very intense with gadgets or other technology. This is a challenge in the learning process. This article aims to produce a learning system with digital literacy based guided inquiry integrated flipped classroom using Discord application on thermochemistry and determining the validity and the practicality level. The study took six months to complete utilizing the Plomp Model and educational design research (EDR). The research steps carried out preliminary research and development of prototyping, this paper is limited to testing the validity and practicality of the developed learning system. The Subject of this research is lectures and teachers as expert review, and 9 students. Data on content and construct validity and practicality were analyzed using Aiken's V formula and practicality percent, respectively. Based on the study's findings, it was determined that the values of 0.84 for both construct and content validity fell into the category of being valid. Results that are practical, scoring 92% in the extremely practical category. Therefore, it was determined that the learning system created was genuine and usable so that its efficacy could be tested for future research